Profil Berpikir Kritis Mahasiswa dalam Penyelesaian Masalah Mikrobiologi - Baitun nikmah; Aminuddin PP; Sri amintarti (Universitas Sebelas Maret, 2017)
Critical thinking is an intellectual process that actively and conceptually conceptualizes, implements, analyzes, synthesizes, and evaluates information gathered or generated from observation, experience, reflection, reasoning, or communication, to guide beliefs and actions. That's because with critical thinking, individuals can be trained to solve problems in different and diverse ways. Giving problems to be solved by the student can track the ability to think critically well, because to solve the problem, one must have the ability to think critically. The purpose of this research is to describe the students' critical thinking profile in solving a valid and reliable microbiological problem. The type of research used is descriptive research using qualitative approach. Subjects in this study were some students of Biology Education of Lambung Mangkurat University who have taken microbiology courses in 2014/2015 academic year, amounting to 6 students, students drawn from 3 high, medium, and low category based on the value of microbiology course. The results of this study indicate that the critical thinking level of Biology University students of Lambung Mangkurat is dominant in critical thinking with critical and critical category. Students who take the course of microbiology certainly have different levels of critical thinking on each person based on written assignments that have been given.